2008
DOI: 10.2460/ajvr.69.9.1123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylprednisolone acetate and glucosamine on proteoglycan production by equine chondrocytes in vitro

Abstract: Methylprednisolone, under noninflammatory conditions present in this study, decreased production of proteoglycan by equine chondrocytes. Glucosamine had a protective effect against inhibition of proteoglycan production at all 3 concentrations studied. This suggested that glucosamine may be useful as an adjunct treatment when an intra-articular injection of a corticosteroid is indicated and that it may be efficacious at concentrations relevant to clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…MPA. In an in vitro study, Byron et al. (2008) showed a significant decrease in proteoglycans in chondrocytes due to MPA administration and Fubini et al.…”
Section: More Recent Research On Beneficial and Deleterious Effects Imentioning
confidence: 97%
“…MPA. In an in vitro study, Byron et al. (2008) showed a significant decrease in proteoglycans in chondrocytes due to MPA administration and Fubini et al.…”
Section: More Recent Research On Beneficial and Deleterious Effects Imentioning
confidence: 97%
“…Corticosteroid treatment, however, is not entirely without potential deleterious effects on cartilage metabolism. A number of in vitro and in vivo studies have demonstrated proteoglycan depletion and/or suppression of proteoglycan (GAG) synthesis in equine cartilage exposed to glucocorticoids . Conversely, chondroprotective effects occur in cytokine or lipopolysaccharide‐stimulated cartilage and chondrocyte cultures .…”
mentioning
confidence: 99%
“…In a previous study, mice injected with methylprednisolone acetate showed a decrease in circulating CD4 + T-lymphocytes, and enabled the propagation of Cryptosporidium parvum in adult mice [24]. Accordingly, because the effects of methylprednisolone are related to a decrease in T-lymphocyte numbers [24,26,27], it is possible that the proliferation of CD4 + and CD8 + T-cells induced by silk protein confers resistance to the immunosuppressive state induced by methylprednisolone.…”
mentioning
confidence: 99%